BENTUK PARTISIPASI MASYARAKAT DALAM PENDIDIKAN DI SMAN 3 TELUK KERAMAT KABUPATEN SAMBAS - Fitri, Fitri; Imran, Imran; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this study isâ€what the community participation was education SMAN 3 Teluk Keramat Sambas. The purpose of research was describe of the forms public education in SMAN 3 Teluk Keramat Sambas. The research used descriptive methods with qualitative study. The data collecting was a student of sociology in academic year 2015 FKIP UNTAN. The technique of data collecting were observation,interview and documentation. Tool of data collecting are observation, guidelines interview, arcives book and notes. The analysis in this research served in a descriptive qualitative by using informans abuot three people. The participation of citizen in education might include people formulating vision and mission education, from meeting and discussion, contribution ideas and respond or aversion towards programs and activites offered by school. The community participation in education system of community participation in accepting new students, procurement of teachers, the procurement facility, infrastructure, and supervision. The form of public participation in evaluation form of criticism and input community, and report evaluationÂ  carried out by which was signed by the school management and community members through school commite..Â Â  Keywords: Community, Education, Participation.